Micro-satellite based diversity estimation of Local hill fowl (Uttara fowl): A unique poultry strain of Uttarakhand - PHANGCHOPI, DONNA; KAUR, NAVNEET; KUMAR, SHIVE; SINGH, LAKSHYA VEER; SOMVANSHI, S. P.S.; SINGH, BALVIR (The Indian Journal of Animal Sciences, 2014)
Nainital and Pithoragarh districts of Uttarakhand in Himalayan region have 2 types of poultry populations. Uttara fowl is reared under backyard system. But no information is available in the literature of Uttara fowl. The aim of the study was to analyze the genetic diversity in Local hill fowl of Uttarakhand (Uttara Fowl) using panel of micro-satellite markers recommended by FAO. The 50 blood samples were collected from randomly selected Uttara fowl. A total of 25 micro-satellite loci were used for this study. All the analyzed 25 loci were polymorphic and a total of 158 alleles were observed in the present study of Uttara Fowl. The observed and expected heterozygosity ranged from 0.292 (LEI-155) to 0.729 (LEI-90) and from 0.414 (MCW–250) to 0.838 (MCW-228) in Uttara fowl, respectively. Wright’s fixation index (Fis) values among loci ranged from –0.085 (for LEI-90) to 0.747(MCW-84). The mean Fis for 25 microsatellite loci was estimated 0.168. Deviation from Hardy-Weinberg equilibrium was observed in Uttara fowl in the commercial cross. The overall population heterozygote deficiency was 0.168. The existence of sufficient genetic diversity within Local hill fowls, estimated through molecular markers analysis would further aid in a conservation scheme, enabling the planning of new strategies for the improvement of in situ conservation schemes.